Rozwój działalności placówek niepublicznych w sektorze ochrony zdrowia - Świderska, Jolanta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The private sector of health care in Poland has been developing rapidly. The number of private medical institutions increased every year. The development of medical private sector is noticeable also in using the latest medical devices. Moreover, medical institutions compete with each other and as a result of this they offer their patients better quality of all providing services. The individual attitude towards each patient gives the private medical institutions chance to fulfill people's expectations. Non-public sector, having a signed agreement with the National Healthcare Fund, can offer services covered by insurance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 668-674